Plan de Manejo para la práctica del Ecoturismo en la comunidad Paquiestancia, parroquia San José de Ayora, cantón Cayambe, provincia de Pichincha – Ecuador - Jácome Quimbita, Rudy Ismael (2021)
This research project was carried out with the purpose of elaborating a management plan for the practice of ecotourism in the Paquiestancia community, through a survey of secondary and primary information and a SWOT analysis, for which we worked on three specific objectives that allowed us to reach the main purpose mentioned above. The current situation of the Paquiestancia community was diagnosed in terms of abiotic factors (climate, soil, geomorphology, hydrology) and biocenosis (flora, fauna, scenic beauty). The tourism carrying capacity of two trails was also measured and the tourism demand of the Cayambe canton was analyzed. Based on the data obtained in the diagnosis, the strengths, weaknesses, opportunities and threats currently facing the study area were identified. To obtain the eco-tourism proposals, the SWOT tool was used to obtain the following eco-tourism proposals in the Paquiestancia community: ecological constructions of two domes with their respective bathrooms, in which one of them will be used as an interpretive center and the second as a restaurant, in addition to the ecological cabins that will be built with ecological bricks, which will allow tourists to spend the night in the place enjoying a spectacular view and comfort. Proposals that respond to the current tourist demand in times of pandemic and that will allow the practice of eco-tourism activities in the study area in an orderly and planned way.